Stigmatization of patients with mental disorders: a comparative study of nurses in forensic psychiatry and inpatient settings - Kılıç-Demir, Barış; Kızılpınar, Selma Çilem (Frontiers in Psychiatry, 2024)
Background: Forensic psychiatric patients require specialized care due to unique challenges in forensic settings. Negative attitudes and beliefs towards mentally disordered offenders can lead to discrimination against patients and are related to worse outcomes. Forensic psychiatric nurses play a crucial role in the treatment of these patients. Aim: This study aimed to investigate the perceptions, attitudes, and beliefs of forensic psychiatric nurses and general medicine nurses towards psychiatric patients and to compare them between nurse groups. Method: The study was conducted with 46 nurses working in the High-Security Forensic Psychiatry Clinic (Mean age: 35.46,SD= 7.16) and 58 nurses working in other inpatient settings (Mean age:36.28, SD=8.78. aged between 18-65 between December 2020 and April 2021 in Turkey. Nurses in the forensic psychiatry clinic were required to have at least 6 months of experience in the clinic.Forensic psychiatric nurses exhibited more positive attitudes towards patients (p<.0001), showing lower tendency to be socially distant (p=.009), higher trust (p<.0001), higher willingness to treat (p<.0001), perceiving patients as threatening (p=.004), and more general positive attitudes. Significant relationships were found between some of the stigma-related scales we used and certain factors. For forensic nurses, being male (p=0.043) and single (p=,025), working long hours (p=.047), and having fewer children (p=.005) were related to more negative perceptions about delinquents. Insufficient knowledge about forensic psychiatry was linked to negative beliefs about mental disorders (p=0.017) and specifically the curability of mental disorders (p=0.008). Having more siblings was related to higher embarrassment about mental disorders (p=.043). For general nurses, having first-degree relatives who receive psychiatric treatment was related to perceiving patients as threatening (p=.021)) and negative perceptions about delinquents (p=.007). Being older was related to more positive beliefs about mental patients' dangerousness (p=.026). Having more siblings was associated with higher trust toward patients (p=0.002). Conclusions: These findings emphasize the importance of addressing stigmatization among healthcare professionals, particularly forensic psychiatry nurses and general nurses. Providing comprehensive training about mental disorders and forensic psychiatry and promoting empathy and understanding can enhance the quality of care for patients with mental illnesses and contribute to better mental health outcomes for society.